TNIP1 in Autoimmune Diseases: Regulation of Toll-like Receptor Signaling - Rambon Shamilov; Brian J. Aneskievich (Journal of Immunology Research)
TNIP1 protein is increasingly being recognized as a key repressor of inflammatory signaling and a potential factor in multiple autoimmune diseases. In addition to earlier foundational reports of TNIP1 SNPs in human autoimmune diseases and TNIP1 protein-protein interaction with receptor regulating proteins, more recent studies have identified new potential interaction partners and signaling pathways likely modulated by TNIP1. Subdomains within the TNIP1 protein as well as how they interact with ubiquitin have not only been mapped but inflammatory cell- and tissue-specific consequences subsequent to their defective function are being recognized and related to human disease states such as lupus, scleroderma, and psoriasis. In this review, we emphasize receptor signaling complexes and regulation of cytoplasmic signaling steps downstream of TLR given their association with some of the same autoimmune diseases where TNIP1 has been implicated. TNIP1 dysfunction or deficiency may predispose healthy cells to the inflammatory response to otherwise innocuous TLR ligand exposure. The recognition of the anti-inflammatory roles of TNIP1 and improved integrated understanding of its physical and functional association with other signaling pathway proteins may position TNIP1 as a candidate target for the design and/or testing of next-generation anti-inflammatory therapeutics.